QRS complex configurations in 12-lead electrocardiograms of dogs with monomorphic ventricular tachycardia or complete bundle branch block - Perego, Manuela; Maffei, Alessandra; Cavallini, Damiano; Santilli, Roberto (Frontiers in Veterinary Science, 2025)
IntroductionThe differentiation between ventricular tachycardias (VT) and supraventricular tachycardias (SVT) with bundle branch block (BBB) is clinically challenging. The aim of the study was to define by the 12-lead-electrocardiogram the QRS complex morphology in monomorphic VT (MVT) and in BBB.MethodsTwelve-lead-electrocardiograms were blindly retrospectively analyzed and categorized in four groups: sinus rhythm with left bundle branch block (SR-LBBB), sinus rhythm with right bundle branch block (SR-RBBB), MVT with RBBB configuration (MVT-RBBB), MVT with LBBB configuration (MVT-LBBB). Measurements were not normally distributed, and they were normalized by Box–Cox transformation. Repeated-measures linear mixed-effects models were constructed according to the 3 measurements performed.ResultsA total of 103 12-lead-electrocardiograms were retrospectively analyzed: 18 SR-RBBB, 18 SR-LBBB, 33 MVT-RBBB, 34 MVT-LBBB. Limb leads concordance was found in 100% of SR-RBBB, 100% of SR-LBBB, 54.5% of MVT-RBBB, 70.6% of MVT-LBBB. Precordial leads discordance was present in 100% of SR-RBBB, 100% of SR-LBBB, 78.8% of MVT-RBBB, 88.2% of MVT-LBBB. The transition point was located at V1-V2 in 100% of SR-RBBB, 100% of SR-LBBB, 50.5% of MVT-RBBB and 71.5% of MVT-LBBB. Positive V1 with M shape morphology was detected in 100% of SR-RBBB and 12% of MVT-RBBB. The mean electrical axis on the frontal plane was -108.15° (−118.29 / −101.52) in RSSR-RBBB, 75.42° (71.78–80.46) in RSSR -LBBB, -93.46° (−102.75/−78.49) in MVT-RBBB and 82.27° (76.85–88.95) in MVT-LBBB.DiscussionIn case of inability to identify signs of atrioventricular dissociation, the presence of standard limb leads discordance, precordial leads concordance or discordance with transition point other than V1-V2, left limb leads and left precordial leads discordance, aVR and V1 discordance and absence of M shape configuration of the QRS complex in lead V1 is likely to be MVT.